Affective bond and attitude towards: mathematics in university students of the Peruvian Amazon. - Paricahua Peralta, Jimmy N.; Estrada Araoz, Edwin G.; Zevallos Pollito, Percy A.; Velasquez Giersch, Libertad; Arellano Mestanza, Frank; Meza Orue, Llen A.; Quispe Aquise, Jhemy; Ulloa Gallardo, Nelly Jacqueline (Archivos Venezolanos de Farmacología y Terapéutica, 2022)
The research was aimed at establishing the relationship between affective bond and attitude towards mathematics in university students in the Peruvian Amazon. The approach was quantitative, the design was non-experimental and the type of design was correlational. The population consisted of 590 students and the sample by 233 students, an amount that was determined by probabilistic sampling. To collect the information, two Likert-type questionnaires were used, instruments with adequate levels of reliability and validity. The results indicate that, using the Spearman correlation test, there is a relationship strength of 0.716 between the affective bond and attitude towards mathematics variables with an effect size of 0.846 and a statistical power of 1. Likewise, the relationship strength between the dimension pedagogical bond and attitude towards mathematics was 0.718 with an effect size of 0.847 and a statistical power of 1. Finally, the strength of relationship between the dimension bond between classmates and attitude towards mathematics was 0.764 with a statistical power of 1. effect size of 0.874 and a statistical power of 1. Finally, it was concluded that the affective bond is directly and significantly related to the attitude towards mathematics.